Animal sculpture from scrap metal: value creation to waste materials - Surachai Donprasri (Asian Creative Architecture, Art and Design : ACAAD, 2025)
This paper presents a creative study utilizing Clive Bell's theory of Significant Form and concepts from artists who use scrap metal to create art. It outlines the design and implementation process in detail, aiming to craft animal-shaped sculptures from scrap metal that are both beautiful and uniquely distinctive. This endeavor reflects the issue of scrap metal waste in Thailand, where the widespread use of steel in the industrial sector results in significant amounts of leftover scrap metal. Most of this scrap metal comes from discarded cars, machinery, and components from the automotive industry, as well as from factories and electrical equipment made of steel. The objective of this research is to create and evaluate the quality of animal-shaped sculptures made from scrap metal. Data were collected from seven experts to assess the suitability and feasibility of these sculptures, including art experts, sculpture specialists, and material research experts in art. The tools used in the research included an assessment form for the suitability and feasibility of creating animal-shaped sculptures from leftover scrap metal. The statistical methods employed for data analysis included mean (X̅) and standard deviation (S). The research findings revealed that the overall assessment of the quality regarding the suitability of the animal-shaped sculptures made from scrap metal was rated at the highest level (X̅ = 4.51, S = 0.51). Similarly, the overall assessment of the feasibility of the animal-shaped sculptures from scrap metal was also rated at the highest level (X̅ = 4.56, S = 0.45).
Keywords: Cultural Heritage Management and Preservation; Conservation Techniques and Studies; Artistic and Creative Research